Adalimumab versus Infliximab Treatment Outcome in Ulcerative Colitis: Application of EQ-5D, Visual Analogue Scale, and IBDQ-9 Measures: A Prospective Observational Study - Karami, Hassan; Azar, Farbod E. F.; Lankarani, Kamran B.; Rezapour, Aziz; Ghahramani, Sulmaz; Baghbanian, Abdolvahab (Current Drug Safety, 2023)
Background: Ulcerative colitis (UC) is a chronic global disease, and its incidence and prevalence are increasing worldwide. Objective: Our objective was to compare the secondary outcome of treatment with Infliximab (IFX) and Adalimumab (ADA) in the UC patients. Methods: This was a one-year prospective observational study of moderate- to -severe UC patients treated with ADA or IFX. Patients' secondary health outcomes were measured using the EQ-5D 3L, EQ-VAS, and IBDQ-9 tools. T-test, Mann-Whitney, chi-square, and Fisher's exact tests were used to compare health-related quality of life (HRQoL) among UC patients. HRQoL predictor variables were identified by multivariate linear regression and multivariate logistic regression. Results: A total of 238 UC patients (patients taking IFX: 78, patients taking ADA: 160) with a mean age of 37.66 and a mean disease duration of 9.29 years were enrolled. The EQ-5D index, EQ-VAS, and IBDQ-9 scores of patients taking IFX were 0.65, 55.93 and, 37.42, respectively. Similarly, patients taking ADA were 0.68, 59.27 and, 36.61, respectively. The highest problem reports were in P/D: 86.1% and A/D: 73.5%. The main independent predictors of HRQoL were: education over 12 years (β = 0.054 [EQ-5D index], β = 13.63 [EQ-VAS], OR: 0.28 [MO], OR: 0.07 [SC]), education between 6-12 years (β = 11.23 [EQ-VAS]), and having
Keywords: IFX